Cohen–Macaulayness versus the vanishing of the first Hilbert coefficient of parameter ideals - Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Ozeki, Kazuho; Phuong, Tran Thi; Vasconcelos, Wolmer V (Journal of The London Mathematical Society-second Series, 2010)
The conjecture of Wolmer Vasconcelos on the vanishing of the first Hilbert coefficient e1(Q) is solved affirmatively, where Q is a parameter ideal in a Noetherian local ring. Basic properties of the rings for which e 1(Q) vanishes are derived. The invariance of e1(Q) for parameter ideals Q and its relationship to Buchsbaum rings are studied. © 2010 London Mathematical Society.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/176-080-348-377-227 tex.type: [object Object]
Keywords: dept.mat